Complexities in diagnosing and treating endophthalmitis in the post stem cell transplant setting. Issue 6 (20th June 2022) - Conlon, Peter; Creedon, Margaret; Houlihan, Elaine; O'Rourke, Sadhbh
Abstract : Endophthalmitis is a rare but sight-threatening manifestation of systemic infection. Immunosuppression is a well-recognised risk factor for development of endophthalmitis. Determining the aetiology can be complex, particularly in the context of immunosuppression, we present the diagnostic and treatment dilemmas associated with a patient who complains of blurred vision 2 weeks following an allogeneic stem cell transplant for refractory Hodgkin's disease. We demonstrate that in the context of immunosuppression post stem cell transplantation, a broad differential should be maintained until a microbiological diagnosis can be confirmed. In particular, we evaluate how clinical suspicion can diverge from typical fundoscopic findings in the diagnosis of endophthalmitis.